Evaluation of Haematopoietic Cells and M/E Ratio in the Bone Marrow of the Partridge (Alectoris chukar) - Tadjalli, M.; Nazifi , S.; Haghjoo, R. (International Journal of Poultry Science, 2011)
In order to study the normal haematopoiesis, cellular components and M/E ratio in the bone marrow of the partridge (Alectoris chukar), bone marrow samples were collected from the proximal tibiotarsus bone of 16 clinically healthy adult partridge (9 male and 7 female). The bone marrow smears were stained using the Giemsa stain. The results indicated that the development and formation of blood cells in the bone marrow of partridge were similar to other birds, whereas the morphology of the cells was similar to chickens, ducks, quail and black-head gull. The mean Myeloid/Erythroid (M/E) ratio was 1.33, the mean erythroid percentage was 39.15%, the mean myeloid percentage was 52.34% and the mean percentage of all other cells percentage was 7.45 %. There was no significant difference in any of the cellular composition between male and female.